Phenolic Content, Antioxidant Capacity, and Antimicrobial Activity of Essential Oil from Habbatus sauda Seed - Nur Farahin, Ishak; Noor Intan Shafinas, Muhammad; Nuraini, Mohd Yusoff; Sook, Fun Pang; Mohd Arman, Abd Kadir; Sazwani, Suhaimi; Hafizah, Ramli; Mohd Faried, Abdullah; Zainal, Giman; Jolius, Gimbun (Oriental Scientific Pub Co, 2014)
This paper presents an extraction and antimicrobial study of essential oil obtainedfrom Nigella sativa seeds. Extraction using polar solvent resulted in higher recovery ofdesired bioactive compounds, thymoquinone and thymol. It was found that extraction ofantioxidant (i.e. Agidol 7) favours aqueous solvent, i.e. 50% ethanol and 50% methanol.The highest TPC, TFC and antioxidant activities were obtained at power 224W andtemperature of 50 °C. This study shows that N. sativaseed oil has an effective antibacterialactivity from the in-vitrostudies. The result showed that the essential oil extracted using n-hexane has the highest (30.17%) effectiveness against E. coli